Corporate Social Responsibility and Accrual-Based Earnings Management: Evidence from Nigeria - Amake, Chinwe Claire; Akogo, Obehioye Usiomon (Mediterranean Journal of Social Sciences, 2021)
This study examines the effect of corporate social responsibility (CSR) on accrual based-earnings management (AEM) nexus. We employed the use of panel least square analysis to test twenty (20) manufacturing companies quoted on the Nigerian Stock Exchange (NSE) for a period of seven (7) years (2013-2019). The study used corporate social responsibility as the independent variable, earnings management as the dependent variable and firm characteristics variables as the control variable. In utilizing the econometric models unreceptive to endogeneity, our result shows that corporate social responsibility has a positive and significant relationship with accrual based-earnings management. In addition, the study finds that firm size and leverage both have a negative and insignificant relationship with accrual based-earning management while profitability has a positive but insignificant relationship with accrual based-earnings management in Nigeria. The results show that more socially responsible firms have higher quality accruals. This suggests that manufacturing firms in Nigeria are likely to engage more in earnings management while increasing their corporate social responsibility. Hence, managers in manufacturing companies in Nigeria, have a tendency to take advantage of corporate social responsibility practices according to the environment they find themselves in. Â  Received: 8 July 2021 / Accepted: 8 August 2021 / Published: 5 September 2021